Step
*
1
1
1
of Lemma
bdd-diff-regular-int-seq
1. k : ℕ
2. b : ℕ
3. f : ℕ+ ⟶ ℤ
4. ∀n,m:ℕ+.  (|(m * (f n)) - n * (f m)| ≤ ((2 * k) * (n + m)))
5. g : ℕ+ ⟶ ℤ
6. ∀n:ℕ+. (|(f n) - g n| ≤ (2 * b))
7. n : ℕ+@i
8. m : ℕ+@i
⊢ ((|m| * |(g n) - f n|) + ((2 * k) * (n + m)) + (|n| * |(f m) - g m|)) ≤ ((2 * (k + b)) * (n + m))
BY
{ (Subst' |(g n) - f n| ~ |(f n) - g n| 0 THENM (RWO "6" 0 THENA Auto)) }
1
.....equality..... 
1. k : ℕ
2. b : ℕ
3. f : ℕ+ ⟶ ℤ
4. ∀n,m:ℕ+.  (|(m * (f n)) - n * (f m)| ≤ ((2 * k) * (n + m)))
5. g : ℕ+ ⟶ ℤ
6. ∀n:ℕ+. (|(f n) - g n| ≤ (2 * b))
7. n : ℕ+@i
8. m : ℕ+@i
⊢ |(g n) - f n| ~ |(f n) - g n|
2
1. k : ℕ
2. b : ℕ
3. f : ℕ+ ⟶ ℤ
4. ∀n,m:ℕ+.  (|(m * (f n)) - n * (f m)| ≤ ((2 * k) * (n + m)))
5. g : ℕ+ ⟶ ℤ
6. ∀n:ℕ+. (|(f n) - g n| ≤ (2 * b))
7. n : ℕ+@i
8. m : ℕ+@i
⊢ ((|m| * 2 * b) + ((2 * k) * (n + m)) + (|n| * 2 * b)) ≤ ((2 * (k + b)) * (n + m))
Latex:
Latex:
1.  k  :  \mBbbN{}
2.  b  :  \mBbbN{}
3.  f  :  \mBbbN{}\msupplus{}  {}\mrightarrow{}  \mBbbZ{}
4.  \mforall{}n,m:\mBbbN{}\msupplus{}.    (|(m  *  (f  n))  -  n  *  (f  m)|  \mleq{}  ((2  *  k)  *  (n  +  m)))
5.  g  :  \mBbbN{}\msupplus{}  {}\mrightarrow{}  \mBbbZ{}
6.  \mforall{}n:\mBbbN{}\msupplus{}.  (|(f  n)  -  g  n|  \mleq{}  (2  *  b))
7.  n  :  \mBbbN{}\msupplus{}@i
8.  m  :  \mBbbN{}\msupplus{}@i
\mvdash{}  ((|m|  *  |(g  n)  -  f  n|)  +  ((2  *  k)  *  (n  +  m))  +  (|n|  *  |(f  m)  -  g  m|))  \mleq{}  ((2  *  (k  +  b))  *  (n  +  m))
By
Latex:
(Subst'  |(g  n)  -  f  n|  \msim{}  |(f  n)  -  g  n|  0  THENM  (RWO  "6"  0  THENA  Auto))
Home
Index